The Relation of Physical Activity with The Quality of Sleep in Adolescents at The Panti Asuhan Yatim Putri Islam RM Suryowinoto Yogyakarta - Murwani, Arita; sutrimo, Sutrimo (Universitas Respati Yogyakarta, 2021)
Sleep is a basic human need, where sleep for every human being will be different for adolescents, needing to sleep around 7-9 hours / day. Adolescents are a group at high risk of experiencing problems in their sleep as a result of damage due to physical activity. There are several factors that can cause the quality of sleep is not disturbed, and physical activity is associated with the disruption of sleep quality. Knowing the relationship between Physical Activity and Sleep Quality in Panti Asuhan Yatim Putri Islam RM Suryowinoto Yogyakarta. This research is a quantitative study with a cross sectional design, the population in this study was 80 foster children in Panti Asuhan Yatim Putri Islam RM Suryowinoto Yogyakarta. The sample in this study using purposive sampling, amounting to 35 respondents. The instrument in this study used the International Physical Activity Questionnaire (IPAQ) and the Pitsburgh Sleep Quality Index (PSQI). Data were analyzed using the Chi-Square test. There are several factors that can cause the quality of sleep to be disturbed, and physical activity is suspected to be associated with disturbed sleep quality. The results showed that there was a relationship between physical activity and sleep quality in Panti Asuhan Yatim Putri Islam RM Suryowinoto Yogyakarta. With the results of the correlation test using the Chi-Square test p = 0.01 (value <0.05). That most of the foster children with high activity with good sleep quality were 1 (2.85%) and 25 (71.4%) had poor sleep quality. These results indicate that there is a significant relationship (p <0.05) between physical activity and sleep quality. Conclusion there is a Relationship between Physical Activity and Sleep Quality in Panti Asuhan Yatim Putri Islam RM Suryowinoto YogyakartaÂ